Retailing - Lewison, Dale M.; DeLozier, M. Wayne (Columbus : Merrill Publishing Company, 1986)
Courses in retailing have never been stronger offerings than they are now. The popularity of courses such as retailing can be attributed to several factors, not the least of which is the job-oriented student. With the sellers' market of the '60s and '70s turning into the buyers' market of the '80's, students today are primarily concerned with getting a good job. The need for courses that enhance their chances of finding entry-level management positions goes a long way to explain the increases in course offerings and enrollments in retailing courses.
Part One. Discovering The World of Retailing -- Part Two. Environmental Scan: Analyzing The Environments of Retailing -- Part Three. Appraising The Retailer's Resources -- Part Four. Market Selection: Evaluating Retail Markets -- Part Five. Retail Mix Management: Implementing The Retailing Mix -- Part Six. Retail Careers: Evaluating Employment Opportunities.
Includes index.
Keywords: RETAIL TRADE